The Impact of Environmental Regulations on Trade Flows: A Focus on Environmental Goods Listed in APEC and OECD - Dai, Zhe; Zhang, Yunzhi; Zhang, Rui (Frontiers in Psychology, 2021)
This paper aims to investigate the impact of environmental regulations on trade patterns, in terms of trade in environmental goods listed APEC and OECD. Environmental goods are defined here as those that enable sustainable growth and reduce pollution from human activity. For this reason, issues on environmental goods can be put at the forefront to analyze the linkage between environmental regulations and trade flows in the perspective of international institutions. Within the framework of a gravity model, a panel data on 112 exporter countries and 53 importer countries is used at a bilateral level over the period 1989-2013 to gain an understanding of this trade-environmental regulation nexus. This paper proxies the environmental policies by employing the z-score, which includes three comprehensive environmental indicators. The findings indicate that the strict environmental policies impede the trade, and this effect is greater in terms of the environmental goods listed in APEC comparing to the ones listed in OECD. Finally, although these stringent environmental regulations reduce the trade flows, they can help to foster the demand for environmentally-friendly products.